Outcome measures in studies on the use of oxytocin for the treatment of delay in labour: A systematic review - BEGLEY, CECILY (My University, 2014)
Abstract Objectives to identify primary and secondary outcome measures in randomised trials, and systematic reviews of randomised trials, measuring effectiveness of oxytocin for treatment of delay in the first and second stages of labour, and to identify any positive health-focussed outcomes used. Design eight relevant citation databases were searched up to January 2013 for all randomised trials, and systematic reviews of randomised trials, measuring effectiveness of oxytocin for treatment of delay in labour. Trials of active management of labour or partogram action lines were excluded. 1918 citations were identified. Two reviewers reviewed all citations and extracted data. Twenty-six individual trials and five systematic reviews were included. Primary and secondary outcome measures were documented and analysed using frequency distributions. Findings most frequent primary outcomes were caesarean section (n=15, 46%), length of labour (n=14, 42%), measurements of uterine activity (n=13, 39%) and mode of vaginal birth (n=9, 27%). Maternal satisfaction was identified a priori by one review and included as a secondary outcome by three papers. No further positive health-focussed outcomes were identified. Key conclusions outcomes used to measure the effectiveness of oxytocin for treatment of delay in labour are heterogeneous and tend to focus on adverse events. Implications for practice it is recommended that, in future randomised trials of oxytocin use for delay in labour, some women-centred and health-focussed outcome measures should be used, which may instil a more salutogenic culture in childbirth.
PUBLISHED
Keywords: Systematic review; Salutogenesis; Health focus; Core outcomes; Delay in labour; Oxytocin; Immunology, Inflammation & Infection; Inclusive Society